2022
DOI: 10.1093/carcin/bgac006
|View full text |Cite
|
Sign up to set email alerts
|

NFE2L3 promotes tumor progression and predicts a poor prognosis of bladder cancer

Abstract: The high incidence and vulnerability to recurrence of bladder urothelial carcinoma (BLCA) is a challenge in the clinical. Recent studies have revealed that NFE2L3 plays a vital role in the carcinogenesis and progression of different human tumors. However, the role of NFE2L3 in bladder cancer has not been elucidated. In this study, NFE2L3 expression was significantly increased in bladder cancer samples. Its high expression was associated with advanced clinicopathological characteristics and was an independent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…NFE2L3 also had promising efficacy in tumor diagnosis, especially in the diagnosis of CHOL, COAD, KICH, READ, and STAD. Thus, our study demonstrated that NFE2L3 expression was upregulated in a variety of cancers and was associated with poor prognosis, consistent with previous reports (Wang et al, 2018;Bury et al, 2019;Dai et al, 2021;Wang et al, 2021;Qian et al, 2022). The above results suggest that NFE2L3 expression was closely related to tumor development and that NFE2L3 can be used as a new biomarker for diagnosis and prognosis in most tumors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…NFE2L3 also had promising efficacy in tumor diagnosis, especially in the diagnosis of CHOL, COAD, KICH, READ, and STAD. Thus, our study demonstrated that NFE2L3 expression was upregulated in a variety of cancers and was associated with poor prognosis, consistent with previous reports (Wang et al, 2018;Bury et al, 2019;Dai et al, 2021;Wang et al, 2021;Qian et al, 2022). The above results suggest that NFE2L3 expression was closely related to tumor development and that NFE2L3 can be used as a new biomarker for diagnosis and prognosis in most tumors.…”
Section: Discussionsupporting
confidence: 92%
“…The NFE2L3 protein is a membrane-bound glycoprotein that targets the endoplasmic reticulum and the nuclear envelope. Recent studies have confirmed that NFE2L3 is linked to certain cancers in humans, including colon cancer, bladder cancer, breast cancer, pancreatic cancer, and liver hepatocellular carcinoma (Wang et al, 2018;Bury et al, 2019;Ren et al, 2020;Dai et al, 2021;Qian et al, 2022). NFE2L3 plays a role in transcription of many biological processes, confers selective growth advantages to cells, and promotes cancer progression, including proliferation, invasiveness, metastasis, and angiogenesis (Kobayashi, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…NFE2L3 exerts a transcription factor function through the CNC‐bZIP domain and affects antioxidation, and lipid metabolism 5–9 . Interestingly, NFE2L3 is overexpressed in various cancers, including breast, colorectal, ovarian, and bladder cancer 10–13 . In malignant tumors, NFE2L3 is cleaved and transported to the nucleus, influencing the occurrence and development of cancer 14 .…”
Section: Introductionmentioning
confidence: 99%
“…3 NFE2L3, as a crucial regulator of the cellular stress response, expressed in diverse tissues of the human, different levels of expression highlight the unique functionality of NFE2L3 in different tissues [4][5][6] . In recent years, a growing number of evidence has indicated the participation of NFE2L3 in the processes of differentiation, inflammation, and carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…James Saliba demonstrated that the deletion of NFE2L3 results in decreased inflammation and a shift in the tumor microenvironment via the IL33 and RAB pathways [7] . Knockdown of NFE2L3 inhibited bladder cancer cell proliferation by inducing the cell cycle and apoptosis [4] . In vitro and in vivo experiments support NFE2L3 as an oncogene involved in the process of tumor formation.…”
Section: Introductionmentioning
confidence: 99%